(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The paper presents the basic theses of Paul Moser’s epistemology of religious beliefs. This author stands against the most popular among analytical philosophers models of argumentism and reformed epistemology. He emphasizes that if God is a personal being, then it is up to Him to determine the conditions and aims of His revelation. According to Moser, God’s purpose would be to reveal His moral perfection and redemption. This is why an experience of being called to a moral conversion by an intentionally acting external agent is the salient evidence justifying the rationality of theism. New epistemological perspective allows polemics with the hiddenness argument formulated by J.L. Schellenberg. Moser, in his refutation of this argument, shows that the existence of cognitively non-resistant non-believers does not prove God’s nonexistence, because lack of cognitive resistance to God is not a sufficient disposition allowing the reception of the transformative gift. The necessary condition for experiencing agapē as a divine self-manifestation is readiness to conform one’s own will to the demands of the divine love.